ASSESSMENT OF DENTAL STUDENTS’ KNOWLEDGE AND CLINICAL DECISION-MAKING IN THE MANAGEMENT OF CARIOUS LESIONS IN PAEDIATRIC PATIENTS: A CROSS-SECTIONAL STUDY - Dr. Arooj Irfan; Maamoor Irfan; Dr. Usman Nazir; Dr. Noor Wajiha; Dr. Raima Bilal; Dr Sajjad Ali Darvesh (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: This study aims to assess dental students’ knowledge and clinical decision-making abilities regarding the management of carious lesions in paediatric patients, highlighting gaps and areas for curriculum improvement.Methods: A cross-sectional survey was conducted among final-year dental students and interns across five dental schools in Khyber Pakhtunkhwa, Pakistan. A validated questionnaire assessed knowledge of caries pathology, preventive strategies, and clinical decision-making scenarios. Data were analysed using descriptive statistics and inferential tests.Results: A total of 312 students participated (response rate: 87%). While 81.4% correctly identified the etiology of early childhood caries, only 53.2% selected appropriate minimally invasive treatments for incipient lesions. Decision-making scores were significantly higher among students who had received additional paediatric dental training (p < 0.01).Conclusion: While general knowledge of caries was satisfactory, notable deficiencies were observed in clinical decision-making regarding evidence-based management approaches. Integrating more case-based learning and hands-on clinical exposure in paediatric dentistry curricula is recommended.